Quarks and gluons in the phase diagram of quantum chromodynamics - Welzbacher, Christian Andreas; Justus Liebig University Giessen (My University, 2016)
In this dissertation we study the phase diagram of strongly interacting matter by approaching the theory of quantum chromodynamics in the functional approach of Dyson-Schwinger equations. With these quantum (field) equations of motions we calculate the non-perturbative quark propagator within the Matsubara formalism. We built up on previous works and extend the so-called truncation scheme, which is necessary to render the infinite tower of Dyson-Schwinger equations finite and study phase transitions of chiral symmetry and the confinement/deconfinement transition. In the first part of this thesis we discuss general aspects of quantum chromodynamics and introduce the Dyson-Schwinger equations in general and present the quark Dyson-Schwinger equation together with its counterpart for the gluon. The Bethe-Salpeter equation is introduced which is necessary to perform two-body bound state calculations. A view on the phase diagram of quantum chromodynamics is given, including the discussion of order parameter for chiral symmetry and confinement. Here we also discuss the dependence of the phase structure on the masses of the quarks.In the following we present the truncation and our results for an unquenched Nf=2+1 calculation and compare it to previous studies. We highlight some complementary details for the quark and gluon propagator and discus the resulting phase diagram, which is in agreement with previous work. Results for an equivalent of the Columbia plot and the critical surface are discussed.A systematically improved truncation, where the charm quark as a dynamical quark flavour is added, will be presented in Ch. 4. An important aspect in this investigation is the proper adjustment of the scales. This is done by matching vacuum properties of the relevant pseudoscalar mesons separately for Nf=2+1 and Nf=2+1+1 via a solution of the Bethe-Salpeter equation. A comparison of the resulting Nf=2+1 and Nf=2+1+1 phase diagram indicates that a dynamical charm quark has no influence on the phase structure.An open question about the phase diagram of quantum chromodynamics is the importance of hadronic degrees of freedom. These are subject to an exploratory study in Ch. 5, where we perform a two flavour calculation and include the nucleon as a degree of freedom in the well-known quark-diquark approximation. Due to the lack of explicit knowledge of in-medium properties of the nucleon, we refer to vacuum results and test their influence by variation. The results show that in this truncation baryons have only very little influence on the phase diagram.This is followed by an approach for a systematic investigation of the quark-gluon vertex Dyson-Schwinger equation at finite temperature. The presented work features an internal model vertex. Calculations taking an unquenched gluon as input are presented, where we compare the quark mass function to results from lattice calculations. We give details about the regularised condensate and study the impact of the different quark flavours and the dependence of the calculation on the chosen internal properties.In the last chapter we perform an investigation of the analytical properties of the quark. The Schwinger function, as the Fourier transform of the Euclidean quark propagator with respect to (imaginary) time, is studied in the vacuum as well as the medium. The spectral function, obtained from correlator data by solving an ill-defined inverse problem, is introduced together with the Rothkopf-Burnier Bayesian reconstruction algorithm, which returns the Bayesian answer to the given inverse problem. The status of the reconstruction for test data is presented and an outline given.

In der vorliegenden Dissertation wird das Phasendiagramm von stark wechselwirkender Materie untersucht. Dazu wird im Rahmen der Quantenchromodynamik der Quarkpropagator über seine quantenfeldtheoretischen Bewegungsgleichungen bestimmt. Diese sind bekannt als Dyson-Schwinger Gleichungen und konstituieren einen funktionalen Zugang, welcher mithilfe des Matsubara-Formalismus bei endlicher Temperatur und endlichem chemischen Potential angewendet wird. Theoretische Hintergründe der Quantenchromodynamik werden erläutert, wobei insbesondere auf die Dyson-Schwinger Gleichungen eingegangen wird. Chirale Symmetrie sowie Confinement und zugehörige Ordnungsparameter werden diskutiert, welche eine Unterteilung des Phasendiagrammes in verschiedene Phasen ermöglichen. Zudem wird der sogenannte Columbia Plot erläutert, der die Abhängigkeit verschiedener Phasenübergänge von der Quarkmasse skizziert.Zunächst werden Ergebnisse für ein System mit zwei entarteten leichten Quarks und einem Strange-Quark mit vorangegangenen Untersuchungen verglichen. Eine Trunkierung, welche notwendig ist um das System aus unendlich vielen gekoppelten Gleichungen auf eine endliche Anzahl an Gleichungen zu reduzieren, wird eingeführt. Die Ergebnisse für die Propagatoren und das Phasendiagramm stimmen gut mit vorherigen Arbeiten überein. Einige zusätzliche Ergebnisse werden präsentiert, wobei insbesondere auf die Abhängigkeit des Phasendiagrammes von der Quarkmasse eingegangen wird.Im Anschluss wird eine systematische Verbesserung der Trunkierung durch die Einführung eines dynamisch betrachteten Charm-Quarks durchgeführt. In dieser Untersuchung ist es insbesondere wichtig, die Skalen richtig zu justieren. Dazu werden die Eigenschaften von pseudoskalaren Mesonen im Vakuum, separat für Nf=2+1 und Nf=2+1+1, reproduziert. Der Vergleich der sich ergebenden Phasendiagramme zeigt, dass das Charm-Quark keinen Einfluss auf die Phasenstruktur hat.Eine wichtige Frage für das Phasendiagramm von stark wechselwirkender Materie betrifft den Einfluss von hadronischen Freiheitsgraden. In einer explorativen Untersuchung für zwei Quarkarten wird der Einfluss des Nukleons in der Quark-Diquark Näherung studiert. Dazu werden unbekannte Abhängigkeiten von Temperatur und chemischem Potential durch Vakuumeigenschaften ersetzt und eine Variation selbiger untersucht. Die Studie zeigt, dass baryonische Freiheitsgrade nur sehr geringen Einfluss auf Phasenübergänge im betrachteten Phasendiagramm haben.Daraufhin wird die reduzierte Dyson-Schwinger Gleichung für den Quark-Gluon-Vertex bei endlicher Temperatur untersucht. Dieser erste Schritt in einer systematischen Studie zeigt wie sich Quarkart sowie Temperaturabhängigkeit auf den Vertex niederschlagen. Es wird offensichtlich, dass eine Rückkopplung der Gleichung für das Gluon notwendig ist.Im letzten Kapitel untersuchen wir analytische Eigenschaften des Quarkpropagators im Vakuum und bei endlicher Temperatur. Dazu wird die Schwinger Funktion, als Fourier-Transformierte des euklidischen Propagators bezüglich (imaginärer) Zeit untersucht. Zudem wird die Spektralfunktion, welche alle Informationen über die analytische Struktur enthält, eingeführt. Die Bestimmung der Spektralfunktion erfordert die Lösung eines inversen Problems, wozu eine Bayes´sche Rekonstruktion genutzt wird. Ergebnisse für die Spektralfunktion von Testdaten, die mithilfe des Rothkopf-Burnier Algorithmus bestimmt wurden, werden präsentiert und notwendige nächste Schritte diskutiert.
Quarks und Gluonen im Phasendiagramm der Quantenchromodynamik
Keywords: Quarks; Gluonen; QCD Phasendiagramm; Quantenchromodynamik; Dyson-Schwinger Gleichungen; Chirale Symmetrie; quarks; gluons; QCD phase diagram; quantum chromodynamics; Dyson-Schwinger equations; chiral symmetry; ddc:530